Participatory methodologies for sustainable technological innovation in cocoa systems: at the Colombian southwest region - Chavarro, Mónica Juliana; Melo, William Felipe; Pulleman, Mirjam Margreet (2022)
In Colombia, cocoa has positioned as a production system that stimulates territorial development processes in areas affected by violence, where a presence of illegal economies exists. It is a crop that enables productive reconversion by offering medium and long-term economic alternatives for farming family’s livelihoods. In this context, the challenge of reconverting to cocoa involves not only the analysis of models, from a technological perspective, but also from the cultural understanding that these transformations imply.